Playing the game: a study of transnational Turkish football fans, imaginations and the internet - McManus, J (2015)
This thesis is about transnational Turkish football communities and how they come to be imagined through internet technologies. The research is based on an ethnography of one particular group of Turkish football fans in Europe. The team is Beşiktaş, one of Turkey's top teams, and the fans make up Çarşi Berlin, their largest supporters' club in Europe. Founded in 2003 in Berlin, the group has grown to consist of 600 members, with branches from London to Switzerland. The thesis explores the internet and its effects at a specific historic juncture on the fashioning of Çarşi Berlin. I approach the topic via three routes, namely, the effects of internet technologies on: football fandom; the spaces in which it occurs; and the cultural forms and practices by which it is instantiated. In the process I contribute to current scholarly debates across sub-disciplines both within and outside anthropology: those of sport and globalisation, enchantment, publics, personhood and the imagination. I argue that football communities are increasingly imagined in ways that are distracted, ephemeral and playful and that, contrary to common conceptions, fun, affect-laden imaginings can have the power to alter conceptions of concepts such as the nation or family. In the process, I contribute greater appreciation of the experience of being a diasporan football fan and its salience for broader understandings of how we imagine belonging in the twenty-first century.